AVALIACÃO DA ATIVIDADE ANTIFÚNGICA E LAXATIVA DA MANGABA (HANCORNIA SPECIOSA) EM PACIENTES COM CONSTIPACÃO - Bruna Magusso Rodrigues (2022)
Constipation is a common condition and its main therapy is the adequate consumption of fiber. Mangaba is a fruit rich in fiber and bioactive compounds, widely used as a by-product by the population of the Cerrado and Pantanal. The aim of this study was to evaluate the effect of this fruit on constipated individuals, the antifungal activity of the pulp in vitro, its proximate composition and antioxidant behavior. For this, female participants (n = 4), with a mean age of 34 ± 13.4 years, ingested mangaba juice at a dose of 3ml of pulp per kg of weight per day for 14 days. Once a day. Participants were evaluated at three times (before the juice, on the 7th day of treatment and 14th day of treatment) by body mass index, 24-hour dietary recall and Rome III criteria questionnaire on number of bowel movements and symptoms related to the act stool and antifungal analyzes were tested at an initial concentration of 20 mg/mL to determine the minimum inhibitory concentration (MIC) and maximum (MFC). In addition to this, analyzes were performed on the fruit pulp referring to physical-chemical analysis, DPPH, bradford and electrophoresis. Data were analyzed using the SigmaPlot program by repeated measures ANOVA and paired t tests. Regarding the number of bowel movements, there was a significant increase (p = 0.001) in the three moments: Before juice (2.5 ± 1.0), 7th day of treatment (3.2 ± 0.9) and 14th day of treatment (5.8 ± 0.9) . Symptoms of strength and feeling of retained stool completely disappeared by M2. Regarding the body mass index, no changes were found and it is assumed that fiber was not, by itself, the main agent responsible for the laxative effect, given that consumption did not increase during the study, the pulp exhibited activity 10 mg CIM antifungal for C. albicans and expressed free radical uptake similar to the control used in the DPPH analysis. In conclusion, mangaba has a laxative effect on women with constipation and growth inhibitory activity for C. albicans, and this activity may be involved in the modulation of the intestinal microbiota and explain the laxative effect found.